2017
DOI: 10.1016/j.jbi.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Development and empirical user-centered evaluation of semantically-based query recommendation for an electronic health record search engine

Abstract: Objective The utility of biomedical information retrieval environments can be severely limited when users lack expertise in constructing effective search queries. To address this issue, we developed a computer-based query recommendation algorithm that suggests semantically interchangeable terms based on an initial user-entered query. In this study, we assessed the value of this approach, which has broad applicability in biomedical information retrieval, by demonstrating its application as part of a search engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 38 publications
(31 reference statements)
0
24
0
Order By: Relevance
“…Baidu is popular in China because of the general unavailability of Google in the country. In a few studies, researchers built [29], prepared [30], or used [31] specialized medical search engines and tested how the results were perceived by users.…”
Section: Introductionmentioning
confidence: 99%
“…Baidu is popular in China because of the general unavailability of Google in the country. In a few studies, researchers built [29], prepared [30], or used [31] specialized medical search engines and tested how the results were perceived by users.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, little research similar to ours can be found, apart from the study used as a comparison [18] . Some other specific systems can be found for searching for literature on Medicine, but they focus on other types of documents, such as Personal Health Records [38][39][40] , or fields like Precision Medicine which requires specific information about, for example, the patient: diseases, genes and mutations, etc. [41] The main drawback of the algorithm described is the extra time necessary to compute the quality-based step with respect to other more optimized systems only based on textual characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Although the search feature is a key tool for efficiently retrieving information from the mass of EHR data, we identified several uses of the search feature that seem to be forced inefficiencies 37 retrieving synonyms and abbreviations, as well as related clinical information. 38,39 The present study contributes to the scant literature on EHR searching, which focuses primarily on homegrown solutions for searching within or across patient records. 16,17,23,40 One of the only prior studies 16 of searches within patient records included 2207 EHR searches by 436 unique users at a single institution and found that the most common searches were for laboratory or test results.…”
Section: Jama Network Open | Health Informaticsmentioning
confidence: 99%